2002
DOI: 10.1149/1.1457206
|View full text |Cite
|
Sign up to set email alerts
|

Study of Membrane Degradation in High-Power Lithium-Ion Cells

Abstract: Impedance spectra of Celgard ® 2300 membranes that were removed from high-power Li-ion cells showed a significant rise in membrane ionic resistivity for cells that were cycled or stored at elevated temperatures. Atomic force microscopy images revealed dramatic changes in membrane surface morphology. Swelling of the membrane polypropylene fibers and the presence of particles of electrode active material in the membrane pores effectively reduced the membrane porosity, and thereby account for the membrane impedan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…Norin et al [14] showed the influence of the separator degradation on the power loss in LiBs that had been exposed to elevated temperatures. The ionic conductivity of all cells decreased, and atomic force microscopy (AFM) revealed a significant loss in porosity.…”
Section: Analysis Of Separatormentioning
confidence: 99%
“…Norin et al [14] showed the influence of the separator degradation on the power loss in LiBs that had been exposed to elevated temperatures. The ionic conductivity of all cells decreased, and atomic force microscopy (AFM) revealed a significant loss in porosity.…”
Section: Analysis Of Separatormentioning
confidence: 99%
“…Norin et al 23,24 have examined the separator membranes (Celgard 2300, PP-PE-PP trilayer structure) that were taken from cells either shallowly (± 1.5% SOC) cycled at 45…”
mentioning
confidence: 99%
“…The causes for the membrane impedance increase were found to be a significant loss in porosity that was revealed by atomic force microscopy. 23 They ascribed this porosity loss to the thermal decomposition of the electrolyte (LiPF 6 -EC-EMC electrolyte, the most widely used commercial electrolyte), the product of which precipitates on the separator and clogs the pores in the separator surface. 24 Although Norin et al's studies well established that the porosity loss leads to an increase of the separator impedance, which accounts for 10% of the cell impedance rise, directly resulting in capacity loss, the behavior of separator itself when stored/cycled at elevated temperature is still unknown.…”
mentioning
confidence: 99%
“…LiF precipitation was also found at the surface of electrodes and in the pores of the separator membrane, which may block the transportation of the Li ϩ ion and increase the resistance of cells. 5,6 Highly reactive PF 5 is produced from both the thermal and hydrolysis reactions and can initiate the polymerization of cyclic carbonate to degrade the electrolyte. 1 The instability of LiPF 6 -based electrolyte is a major factor for degradation of lithium batteries operating at elevated temperatures.…”
mentioning
confidence: 99%
“…7 Their molecular dynamic simulations show that the average distances between the Li ϩ cation and the F atoms in the PF 6 Ϫ anion in the presence of anion receptors ͑aza ether compounds͒ are much larger than the absence of the aza ether compounds. They postulated that this enlarged distance suppresses the reactivity of the Li ϩ cation and F atoms.…”
mentioning
confidence: 99%